Étude de la motivation autodéterminée des étudiants dans le contexte d'une activité pédagogique faisant appel à Facebook comme plateforme d'échange - Hassen Ben Rebah; Georges Modeste Dabove (Centre National d'Enseignement à Distance, 2017)
This paper studies the self-determined motivation among a group of students enrolled at the Higher Institute of Technological Studies of Mahdia (ISETM) in the context of an educational activity using Facebook as a platform for exchange and collective construction of knowledge. In this work, we resorted to self-determination theory of Deci and Ryan (1985) which gives a pertinent evaluation framework of self-determined motivation among our target audience in a learning environment based on ICT. The results indicate that students constituting a group are motivated to use Facebook for learning purposes. Ultimately, the use of Facebook as an educational artifact is particularly appreciated by students to enable them to acquire new knowledge and have the satisfaction of advancing skills. Given the motivational aspect offered the use of this social network in university teaching, we can deduce that it has a huge potential for a massive and effective integration of ICT in higher education.